The Mediating Role Of Role Ambiguity In The Relationship Between Job-Relevant Information And Public Accounting Firm Performance - Andi Agus; Anwar (LPPM STIEM, 2026)
This paper attempts to empirically examine the effect of job-relevant information on the performance of public accounting firms by using mediating variables of role ambiguity. This study draws on a sample of 120 auditors working in public accounting firms in Jabodetabek-Indonesia, using random survey methods. The primary technique for analyzing the data is Structural Equation Modeling.The test results show that job-relevant information has a negative effect on role ambiguity. Role ambiguity has a negative effect on the performance of public accounting firms. Job-relevant information has a positive effect on the performance of public accounting firms. Role ambiguity mediates the effect of job-relevant information on the performance of public accounting firms. The findings emphasize the importance of job-relevant information in performing auditing tasks.Role ambiguity in this study serves to amplify the influence of job-relevant information on the performance of public accounting firms.